2017
DOI: 10.1177/2045125317737264
|View full text |Cite
|
Sign up to set email alerts
|

The role of selective serotonin reuptake inhibitors in preventing relapse of major depressive disorder

Abstract: The objective of this review was to evaluate the efficacy of selective serotonin reuptake inhibitors (SSRIs) and SSRIs compared with other treatment modalities in preventing relapse after an episode of major depressive disorder (MDD). An Ovid MEDLINE and PsycINFO search (from 1987 to August 2017) was conducted using the following terms: selective serotonin reuptake inhibitors, antidepressants, depression, prevention, prophylaxis, relapse and MDD. Using predefined criteria, two authors independently selected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…The experimental mice with or without LPS and/or SB treatment were divided into 8 groups (n = 10/group): group I was treated with vehicle (dimethyl sulfoxide [DMSO]:PBS [1: 1]) of SB for 10 consecutive days, and then treated with saline 30 min after the last vehicle injection; group II, III and IV were treated with 20 mg/ kg of fluoxetine (DMSO:PBS [ for 10 consecutive days, respectively, and then treated with saline 30 min after the last drug injection; group V was treated with vehicle (DMSO:PBS [1: 1]) of SB for 10 consecutive days, and then treated with 0.83 mg/kg of LPS 30 min after the last vehicle injection; this dosage of LPS was selected according to our previous studies [6,7]; group VI was treated with 20 mg/kg of fluoxetine for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last fluoxetine injection; group VII was treated with 100 mg/kg of SB for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last SB injection; and group VIII was treated with 300 mg/kg of SB for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last SB injection. The timeline for the tail suspension test (TST), forced swim test (FST), sucrose preference test (SPT), open field test (OFT), and biochemical assays were outlined in Figure 1.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental mice with or without LPS and/or SB treatment were divided into 8 groups (n = 10/group): group I was treated with vehicle (dimethyl sulfoxide [DMSO]:PBS [1: 1]) of SB for 10 consecutive days, and then treated with saline 30 min after the last vehicle injection; group II, III and IV were treated with 20 mg/ kg of fluoxetine (DMSO:PBS [ for 10 consecutive days, respectively, and then treated with saline 30 min after the last drug injection; group V was treated with vehicle (DMSO:PBS [1: 1]) of SB for 10 consecutive days, and then treated with 0.83 mg/kg of LPS 30 min after the last vehicle injection; this dosage of LPS was selected according to our previous studies [6,7]; group VI was treated with 20 mg/kg of fluoxetine for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last fluoxetine injection; group VII was treated with 100 mg/kg of SB for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last SB injection; and group VIII was treated with 300 mg/kg of SB for 10 consecutive days, and then treated with LPS (0.83 mg/kg) 30 min after the last SB injection. The timeline for the tail suspension test (TST), forced swim test (FST), sucrose preference test (SPT), open field test (OFT), and biochemical assays were outlined in Figure 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…Its pathogenesis has been well documented in the previous studies [1] and has been confirmed to be associated with repeated exposure to harmful stress, which may include a variety of social and un-social stimuli, such as poor parental care [2], drug addiction [3], and heart surgery [4]. The presently available antidepressants in clinic, such as the selective monoamine oxidase inhibitors and the serotonin reuptake inhibitors, ameliorate depressive symptoms mainly through rectifying the monoamine dysfunction in the brain [5][6][7]. However, during the clinical application these agents exhibit numerous side effects [8], and only one third of patients acquire effective responses to these antidepressants [9].…”
Section: Introductionmentioning
confidence: 95%
“…Selective serotonin reuptake inhibitors (SSRIs) are commonly used as first-line treatment for MDD 3 . They are thought to increase the extracellular availability of the neurotransmitter serotonin by limiting its reabsorption into presynaptic cells, increasing serotonin levels in the synaptic cleft, and making it available for postsynaptic receptor binding 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, the slow effect and relapse, leading to long-term and reduplicated uses, create a severe disadvantage for patients and even build the barriers for SSRIs applications. [4,5] Therefore, it suggests to further reveal the underlying mechanisms in details other than simply descriptions of decreased 5-HT in the occurrence of MDD.…”
Section: Introductionmentioning
confidence: 99%